2012
DOI: 10.1055/s-0031-1283941
|View full text |Cite
|
Sign up to set email alerts
|

Erotischer Fotoaustausch unter Jugendlichen: Verbreitung, Funktionen und Folgen des Sexting

Abstract: Übersicht: Der private Austausch selbst produzierter erotischer Fotos per Handy oder Internet wird als "Sexting" bezeichnet. In der Öffentlichkeit wird Sexting primär als mediales Problemverhalten Jugendlicher diskutiert. Medienpädagogische Kampagnen betonen die Gefahren erotischen Fotoaustauschs und fordern Jugendliche zur Sexting-Abstinenz auf. Der vorliegende Beitrag beschreibt das Phänomen Sexting erstmals umfassend aus sozialpsychologischer Perspektive: Wie verbreitet ist Sexting? Welche Funktionen erfüll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 8 publications
0
7
0
7
Order By: Relevance
“…Firstly, it is hypothesized that bullies try to receive sexts from others to embarrass and humiliate the sender, i.e., by forwarding the sexts to others who are not supposed to see the pictures. Secondly, bullies might use sexts more frequently for establishing relationships, to show off, to flirt and to become sexually aroused [41]. In support of the second explanation, previous research showed that, bullies often start dating earlier and being highly relationship oriented [34].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Firstly, it is hypothesized that bullies try to receive sexts from others to embarrass and humiliate the sender, i.e., by forwarding the sexts to others who are not supposed to see the pictures. Secondly, bullies might use sexts more frequently for establishing relationships, to show off, to flirt and to become sexually aroused [41]. In support of the second explanation, previous research showed that, bullies often start dating earlier and being highly relationship oriented [34].…”
Section: Discussionmentioning
confidence: 88%
“…Receiving and sending of sexually explicit messages or nude, semi-nude selfies (digital images of one's self), videos or texts via ICTs, is usually defined as sexting [40,41]. There are a variety of reasons why adolescents engage in sexting.…”
Section: Sextingmentioning
confidence: 99%
See 1 more Smart Citation
“…Was bleibt, sind aber noch die zwischenmenschlichen Sexkontakte auf Distanz. Diese sind seit den 1990er-Jahren bekannt unter Stichworten wie Cybersex, virtueller Sex, Chatsex, Camsex oder neuerdings auch Sexting (Courtice und Shaughnessy 2017;Dannecker und Lemke 2017;Döring 2000Döring , 2012aDöring , 2014aKoops et al 2018;Shaughnessy et al 2011). Angesichts der Corona-Kontaktverbote erfreuten sich solche medienvermittelten zwischenmenschlichen Sexkontakte plötzlich besonders großer Beliebtheit und wurden öffentlich so stark diskutiert, dass im März 2020 in den Medien ein Mehr-Telefonsex-und-mehr-Onlinesex-Narrativ als das populärste Partnersex-Narrativ (vertreten in 21.6 % der Medienbeiträge im Sample, siehe oben ▶Tab.…”
Section: Das Weniger-unverbindlicher-partnersex-narrativunclassified
“…These activities actually confirm their masculinity, and they acquire approval and admiration from their peers (Ringrose et al, 2012). The people around tend to see and describe girls who participate in these or similar activities as insecure, with a lack of self-respect and/or people prone to promiscuous behaviour (Döring, 2012;Lippman & Campbell, 2014;Ringrose et al, 2012;Walker et al, 2013). People also show a tendency towards seeing girls as those who through reckless and irresponsible behaviour are seeking the attention of young men in the wrong way (Hasinoff, 2013;Karian, 2012;Ringrose et al, 2012Ringrose et al, , 2013.…”
Section: The Individual Determinants Of Sextingmentioning
confidence: 99%